Metabolism of Phloridzin by Erwinia herbicola: Nature of the Degradation Products, and the Purification and Properties of Phloretin Hydrolase - Chatterjee, A. K. (1969)
Erwinia herbicola Y46 degrades phloridzin to yield phloretin, phloroglucinol, and phloretic acid, when grown on defined medium containing phloridzin as the sole source of carbon. The identities of the intermediates isolated from culture filtrates were established by co-chromatography and by ultraviolet absorption spectra. Only 3 of 11 strains of this species, and none of the 12 species of bacterial phytopathogens tested could effect this breakdown. Some of the latter organisms possessed β-glucosidase activity which liberated d-glucose from phloridzin. The enzyme phloretin hydrolase was purified from cells of E. herbicola Y46 grown on Yeast Beef Broth, by treatment of crude extracts with protamine sulfate, ammonium sulfate precipitation, elution from calcium phosphate gel, elution from diethylaminoethyl-cellulose, and concentration by ultrafiltration. The final preparation was free of β-glucosidase, had a specific activity of 213 units per mg of protein, and represented a 142-fold purification over the crude extract. The enzyme had a pH optimum of 6.7 to 6.8, and produced only phloroglucinol and phloretic acid as products of phloretin breakdown, there being an equimolar relationship between the cleavage of phloretin and the formation of the products. The Michaelis constant (K(m)) for the enzyme with phloretin as substrate was 3.8 × 10(−5)m, and the enzyme was sensitive to Hg(2+) and Cu(2+) ions. Phloroglucinol, phloretic acid, p-chloromercuribenzoate and iodoacetamide were without effect on the activity. The enzyme did not react with phloridzin, naringin, or naringenin. The physiological significance of the results is discussed.